Approximate quantum cloning with nuclear magnetic resonance. - Cummins, H; Jones, C; Furze, A; Soffe, N; Mosca, M; Peach, J; Jones, J (2002)
Here we describe a nuclear magnetic resonance (NMR) experiment that uses a three qubit NMR device to implement the one-to-two approximate quantum cloning network of Buzek et al. [Phys. Rev. A 56, 3446 (1997)]. As expected the experimental results indicate that the network clones all input states with similar fidelities, but as a result of decoherence and incoherent evolution arising from B(1) inhomogeneity the total fidelity achieved does not exceed the measurement bound.